2019
DOI: 10.3892/ijmm.2019.4449
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy and NKG2D system in brain�metastases: Analysis of immunogenicity

Abstract: Patients with breast cancer (Bc) and lung cancer (Lc) are prone to developing brain metastases, which are associated with devastating prognoses. dormant tumor cells, a population of non-apoptotic quiescent cells and immunological escape mechanisms, including the Natural Killer Group 2 member d (NKG2d) receptor-ligand system, represent potential mechanisms of tumor recurrence. To date, the immunological characteristics of dormant tumor cells concerning the NKG2d system in cerebral malignancies are mostly unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…In addition, studies in brain tumours revealed the role of B7-H3 in regulating cancer stemness and metabolism [49]. As the pathogenesis of BrM involves brain metastatic cells undergoing cycles of dormancy, neural microenvironment adaptation, and brain invasion [50,51], it is possible that B7-H3 may be involved in these mechanisms for cells originating in the breast.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies in brain tumours revealed the role of B7-H3 in regulating cancer stemness and metabolism [49]. As the pathogenesis of BrM involves brain metastatic cells undergoing cycles of dormancy, neural microenvironment adaptation, and brain invasion [50,51], it is possible that B7-H3 may be involved in these mechanisms for cells originating in the breast.…”
Section: Discussionmentioning
confidence: 99%
“…In glioblastoma, major histocompatibility complex class I molecules expressed on tumor cells bind to NK cell inhibitory receptors and suppress their immune function 37 , 38 . Gliomas and brain metastases can further downregulate the expression of activating receptors, such as NK Group 2 member D (NKG2D), to evade immune activation of host NK cells 39 , 40 . The tumor microenvironment in pediatric solid tumors is rich in immunosuppressive molecules such as transforming growth factor beta (TGFβ) 41 , 42 , adenosine 43 , PGE2 44 , as well as indoleamine 2,3-dioxygenase (IDO) 45 .…”
Section: Nk Cells In the Brain Tumor Microenvironmentmentioning
confidence: 99%
“…Interestingly, NK cells can also provide a variety of cytokines (e.g., CXCL10) that enhance the aforementioned ability of CD8 and CD4 lymphocytes to induce dormancy in a model of acute myeloid leukemia (AML)( Saudemont et al, 2005 ), however, this study shows only correlation of NK ligand expression with dormancy markers in dormant tumor masses without showing function of NK. Additionally, a recent study showed co-localization of dormancy markers (e.g., H2BK or PDGFB) with ligands of the NK group 2 member D receptor (MICA, MICB, or ULBP1 and 2) in patients with brain metastasis from lung and breast cancers, suggesting that these mechanisms may co-operate in maintaining metastatic dormancy ( Fluh et al, 2020 ).…”
Section: Microenvironmental Regulation Of Dtc Dormancymentioning
confidence: 99%